Luxembourg : 2009 Article IV Consultation; Staff Report; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for Luxembourg. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2009)
The adverse impact of the crisis on Luxembourg's growth outlook is partly mitigated by the authorities' well-conceived fiscal policy response. The staff report for Luxembourg's 2009 Article IV Consultation highlights economic developments and policies. It combines substantial fiscal stimulus, including subsidies aimed at stabilizing employment, with the full functioning of the automatic stabilizers. All major expenditure components of GDP are likely to be adversely affected by the financial crisis, waning confidence, and euro area recession.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet